Aspek-Aspek Bioetis dalam Pelayanan Pastoral Care Lintas Agama - Sri Sumiyati, Teresia; Siwi Padmawati, Retna; Boromeus Kusmaryanto, Carolus (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2026)
Pastoral care as a form of spiritual care at Charitas Hospital Palembang is carried out holistically, taking into account all aspects of patients’ lives regardless of their religious background, ethnicity, race, or social status. The study aims to explore and analyse the bioethical aspects that arise in interfaith pastoral care, particularly in the context of a Catholic hospital serving a pluralistic community. This study used a descriptive qualitative design involving 24 informants consisting of hospital pastoral care officers, interfaith religious leaders, health workers (doctors and nurses), hospital directors, and inpatients. Data collection techniques included semi-structured interviews, observation, and documentation, which were then analysed thematically. The results showed that bioethical aspects such as respect for autonomy, non-maleficence, beneficence, and justice have been applied in pastoral care services, despite challenges related to religious diversity, limited training, and public perception. The combination of Beauchamp and Childress’ bioethical principles with Sulmasy’s spiritual care ethics proved to be highly relevant, as it prioritises a holistic and patient-centred approach. Interfaith pastoral care services that respect ethics and are inclusive support more meaningful, humane and dignified healthcare.